Decorating protein hydrogels reversibly enables dynamic presentation and release of functional protein ligands on protein hydrogels. Issue 84 (7th October 2019) - Wang, Ruidi; Fu, Linglan; Liu, Junqiu; Li, Hongbin
Abstract : Utilizing protein fragment reconstitution, we demonstrate the reversible and repeatable functionalization of protein hydrogels. Abstract : Utilizing protein fragment reconstitution, we demonstrate the reversible and repeatable functionalization of protein hydrogels. This novel method enables the presentation and release of functional protein ligands on protein hydrogels.